Design and first development of an automated real‐time safety management system for construction sites - Giretti, Alberto; Carbonari, Alessandro; Naticchia, Berardo; Grassi, Mario De (Journal of Civil Engineering and Management, 2009)
This paper reports a feasibility study which addressed the development of a new, advanced system mainly devoted to automatic real‐time health and safety management on construction sites. The preliminary analyses and experiments described in this paper concern two of the most important functionalities which must be included in the system’s final release. The first functionality consists in real‐time position‐tracking of workers involved on construction sites and the second ‐ in a software tool for the prevention of non‐authorized access to dangerous zones. This research step is part of a vaster, ongoing research project, addressing the development of a new generation of advanced construction management systems which allow real‐time monitoring and coordination of tasks, automatic health and safety management, on‐site delivery of technical information and the capture of “as‐built” documentation. This paper focuses mainly on the development of a reliable methodology for real‐time monitoring of the position of both workers and equipment in outdoor construction sites by applying Ultra Wide Band (UWB) based technologies. This positioning system was then interfaced with a software tool which performs virtual fencing of pre‐selected, dangerous areas. Guidelines for the design of the receivers’ topology will be addressed and the results of measurements recorded on a typical medium‐sized block of flats, during different phases of the construction progress will be summed up. Finally, the preliminary experimental results obtained by the virtual fencing application tool will be presented and used to plan future research objectives. Santrauka Straipsnyje aptartos naujos automatinės darbo ir saugos valdymo sistemos statybos aikštelėje kūrimo galimybės. Aprašytos preliminarios analizės ir eksperimentai – du pagrindiniai veiksniai, kurie turi būti įtraukti į galutinį sistemos variantą. Pirmasis veiksnys susijęs su statybos aikštelės darbininkų padėties realiu laiku nustatymu. Kompiuterine programa ribojamas jų patekimas į pavojingas neleistinas zonas. Šie tyrimai yra didelio besitęsiančio projekto dalis. Projektas susijęs su naujos kartos statybos valdymo sistemos kūrimu. Sistema leis kontroliuoti statybos eigą realiu laiku, užtikrinti automatinį darbų saugos valdymą, techninės informacijos ir dokumentacijos gavimą. Straipsnyje pagrindinis dėmesys sukoncentruotas į patikimos metodikos kūrimą. Taikant šią metodiką ir ultraplačiajuosčio bevielio ryšio (angl. Ultra Wide Band (UWB)) technologiją, galima bus nustatyti darbininkų ir įrangos padėtį atvirose statybos aikštelėse realiu laiku. Ši nustatymo sistema per grafinę terpę yra sujungta su programine įranga, kuri sukuria virtualų aptvarą iš anksto nurodytoms pavojingoms zonoms. Pateiktos imtuvo topologijos projektavimo rekomendacijos. Įvertinti tipinių vidutinio dydžio butų blokų užfiksuotų matavimų rezultatai skirtingais statybos etapais. Pateikti preliminarūs eksperimentiniai rezultatai, gauti įvedus virtualaus aptvėrimo koncepciją. Šie rezultatai bus panaudoti planuojant būsimų tyrimų tikslus. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: statybos aikštelės, darbų saugos valdymas, rizikos valdymas realiu laiku, ultraplačiajuostis bevielis ryšys, pozicijos nustatymas, elgsenos modeliai.